KESULITAN-KESULITAN DALAM IMPLEMENTASI KURIKULUM MATA PELAJARAN IPS SMP - Eni Cahya Wijayati; I Nyoman Sudana Degeng; Sumarmi Sumarmi (Pascasarjana Universitas Negeri Malang, 2016)
The implementation of curriculum is an effort to implement a curriculum that has been designed. The main purpose of this article is to reveal the factors of the difficulties in implementation of curriculum of social studies in junior high school. This research uses descriptive research with a qualitative approach. The data collection used interviews, observation and documentation. The data were analyzed through data reduction, presentation, and conclusion. The subject in this study is teachers of social studies at junior high school. Based on the analysis was found that the assessment is complicated, amount of material makes time become insufficient, the implementation scientific approach is mainly on reasoning and analyzing that is not done, the difficult to combine the material into integrated social subject, and the lack of infrastructure is also the cause of the difficulties of social subject teachers in the implementation of curriculum. Implementasi Kurikulum adalah upaya penerapan kurikulum yang telah dirancang. Tujuan utama penulisan artikel ini mengungkap faktor-faktor kesulitan dalam implementasi Kurikulum mata pelajaran IPS SMP. Penelitian ini menggunakan penelitian deskriptif dengan pendekatan kualitatif. Pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Data dianalisis melalui reduksi data, sajian data, dan penarikan kesimpulan. Subjek dalam penelitian ini adalah guru mata pelajaran IPS di SMP. Berdasarkan hasil analisis didapatkan bahwa penilaian yang rumit, banyaknya materi sehingga waktu menjadi tidak cukup, penerapan pendekatan saintifik terutama pada menalar dan menganalisis tidak terlaksana, sulitnya memadukan materi menjadi IPS Terpadu, dan kurangnya sarana prasarana menjadi penyebab kesulitan yang dihadapi guru mata pelajaran IPS dalam implementasi kurikulum.